South Africa : Social Assistance Programs and Systems Review - World Bank (World Bank, Washington, DC, 2021)
Despite being an upper middle income country, South Africa’s high inequality and the long-lasting legacies of apartheid mean that the country is faced with numerous development challenges, many of which are characteristic of countries with much lower incomes. This paper focuses on social assistance and, specifically, the system of social grants in South Africa. This report aims to review the social assistance system in South Africa to first understand how it functions and what kinds of benefits it provides through which programs, and what tools and systems it uses to do so. Second, it reviews the performance of the system in terms of coverage, targeting, benefit incidence, adequacy, cost-effectiveness, and outcomes. Third, it assesses the extent to which the system is aligned and equipped to address the so called “triple challenge” of poverty, inequality, and unemployment as shown by data. It also reviews the limitations in the design, delivery systems, and institutional coordination at different administrative levels. Based on the analysis, this paper provides some recommendation for what adjustments and improvement the South African social assistance system could undertake in the next fi ve years in order to better align the system address the structural causes of poverty and inequality in addition to providing relief and income support. The report concludes and provides some policy and programme recommendations for the future.